Growth mindset investigation in english classes grounded on the sociodiscursive interactionism - Stankoski, Camila Ribas (2022)
The present research intended to investigate basic education English teachers’ representations about public state school teaching conditions and how these conditions might affect their mindsets and, consequently their pedagogical practices. Hence, to achieve this main goal, specific objectives were established: a) to investigate the difficulties faced by the English teachers who participated in this research taking into account their specific contexts of work; and, b) to identify and analyze changes in participant teachers’ mindsets, after their experience in the outreach course. Aiming to provide an in-service teaching education opportunity for English teachers from the Southwest region of Paraná and also to generate data for this research, a two-month outreach course, comprised of eight one-hour meetings from August to September 2021, was offered to three public in-service English teachers. It had as main goals to learn about teachers’ professional contexts, as well as to discuss relatively new psychological and methodological concepts, which would posteriorly be applied in their classrooms. All meetings were audio-recorded and oral discussions transcribed. Therefore, research was constituted of a great amount of oral transcriptions that were divided into three sets of data corresponding to: a) teachers’ representations on their context of work; b) teachers’ representations on possible classroom projects; and c) teachers’ representations on an applied classroom project. These three sets of data were analyzed by means of a qualitative-interpretive perspective (DENZIN; LINCOLN, 2007), involving different types of analysis based on Sociodiscursive Interactionism (BRONCKART, 2012). Results indicate that English teachers face adverse conditions of different natures in their work environment, such as: conditions caused by the pandemic; school conditions previous to the pandemic; teachers’ professional and subjective difficulties; and students’ classroom behaviors. These conditions are likely to negatively affect their mindsets, since they are connected to teachers’ lack of motivation to prepare classes and reflect on their pedagogical practices, leading them to avoid trying to use different classroom methodological procedures with their students, which perpetuates the traditional teaching approach in the English classes.